Eksperimentasi Pembelajaran Matematika Menggunakan Model Kooperatif Tipe Student Teams Achievement Divisions (Stad) dan Think-Pair-Share (Tps) pada Materi Pokok Persamaan Garis Lurus Ditinjau dari Kreativitas Siswa - Edy Suprapto; Imam Sujadi; Mania Roswitha (Jurnal Penelitian Pendidikan, 2012)
Abstract:This research aims to know the difference of influlence in learning models, creativity, andits interaction toward student’s learning achievement on the subject matter: equations ofa straight line. This research is a quasi experimental research with factorial design of3x3. The population is eight grade students of Junior high School in Madiun. The samplesare taken using stratified cluster random technic. Sample of the research is 283 students.The collecting data instruments is a questionnaire on creativity and learning mathematicsachievement test. The trial test of instrument of the questionnaire includes the contentvalidity, the internal consistency, and realibility. The trial test on the achievement oflearning on mathematics includes the content validity, the difficulty level, thediscrimination power, and realibility coefficient. The Data analysis technique usedconsists of: balance, precondition analysis (Normality and Homogenity). Hypothesisanalysis test uses two-ways variant analysis with different cells.The results of the research are: (1) The students who are learning withcooperative model of STAD have better achievement than the students who are givenconventional learning, and the students who are given cooperative model of STAD havethe same achievement with the students who are given cooperative model of TPS; (2) Thestudents with high creativity have better achievement than the students who have lowercreativity (middle and low), the students with middle creativity have the sameachievement with the students who have low creativity, (3) On students with highcreativity, implementation learning models of STAD, TPS, and conventional give thesame effect; On students with middle creativity, implementation of cooperative learningwith STAD model gives the same effect as good as the TPS model, implementation ofcooperative learning with STAD models provides a better effect than conventionallearning, and implementation of cooperative learning with TPS model gives a bettereffect than conventional learning; On students with low creativity, implementation ofcooperative learning with STAD and TPS models give the same effect, implementation ofcooperative learning with STAD model and conventional learning also provide the sameeffect, and implementation of cooperative learning with TPS model gives a better effectthan conventional learning.